2015
DOI: 10.1074/jbc.m114.603365
|View full text |Cite
|
Sign up to set email alerts
|

The Allosteric Regulatory Mechanism of the Escherichia coli MetNI Methionine ATP Binding Cassette (ABC) Transporter

Abstract: Background:The MetNI transporter drives methionine import against its concentration gradient and regulates intracellular methionine levels. Results: Methionine is a noncompetitive inhibitor of MetNI ATPase activity, binding the transporter at two allosteric sites. Conclusion: MetNI regulates intracellular methionine concentrations via allosteric regulation. Significance: Regulation of methionine import at the protein level may minimize wasteful consumption of ATP when adequate intracellular supplies are availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
16
2
Order By: Relevance
“…As we held expression levels constant with an exogenous promoter, we demonstrated that a phoU deletion mutant accumulated Pi at a higher rate than cells expressing the pstSCAB genes and phoU. Other ABC transporters, such as the methionine transporter, have regulatory domains that respond to the cytoplasmic concentrations of transported substrates and function as sites of allosteric inhibition of transport [86][87][88]. We proposed that PhoU plays a similar role for Pi transport in E. coli.…”
Section: The Response To High Levels Of Extracellular Pimentioning
confidence: 88%
“…As we held expression levels constant with an exogenous promoter, we demonstrated that a phoU deletion mutant accumulated Pi at a higher rate than cells expressing the pstSCAB genes and phoU. Other ABC transporters, such as the methionine transporter, have regulatory domains that respond to the cytoplasmic concentrations of transported substrates and function as sites of allosteric inhibition of transport [86][87][88]. We proposed that PhoU plays a similar role for Pi transport in E. coli.…”
Section: The Response To High Levels Of Extracellular Pimentioning
confidence: 88%
“…38,45 In addition to substrate-binding protein mediated activation, ABC transporters can also be regulated by additional domains, for example, regulatory domains that control the interaction of the NBDs in cis. 46,47 Exporters can also be allosterically regulated by the respective ligands. [48][49][50] In the inward-facing conformation, the NBDs can be quite separated, suggesting that ligand binding at the inward-facing cavity in the TMDs helps trigger a conformational change that brings the NBDs in closer proximity.…”
Section: Abc Transportersmentioning
confidence: 99%
“…It is therefore of no surprise that decades of research were dedicated to understanding their structure and function. Despite the diversity of their physiological roles and substrate recognition profiles (12)(13)(14)(15)(16)(17) ABC transporters share a common basic architecture, minimally comprising of two intracellular nucleotidebinding domains (NBDs) that bind and hydrolyze ATP, and two transmembrane domains (TMDs) that form a substrate-translocation pathway (18)(19)(20)(21). ATP is bound at two composite sites formed at the interface of the NBDs, and proper formation of the ATP-binding sites requires that the NBDs close into a tight head-to-tail sandwich (22).…”
Section: Introductionmentioning
confidence: 99%